2010
DOI: 10.1590/s0004-28032010000300008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of serological markers for celiac disease (IgA and IgG class antigliadin antibodies and IgA class antiendomysium antibodies) in patients with autoimmune rheumatologic diseases in Belo Horizonte, MG, Brazil

Abstract: Positive AGAA, AGAG or EmA results are probably nonspecific for the presence of celiac disease among autoimmune rheumatologic disease patients. The intake of prednisone and immunosuprressant drugs seems to reduce the prevalence of IgA EmA, but it does not interfere with antigliadin antibodies tests.Further studies are required to estimate more accurately the prevalence of this disease in rheumatologic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…The consequences of undiagnosed CD are not well described. Studies have shown that patients with CD have an increased risk of other autoimmune diseases and gastrointestinal cancer [ 26 , 27 , 28 ]. One study found a fourfold increased mortality in persons with untreated and undiagnosed CD [ 29 ], whereas others reported mortality rates to be relatively similar to those observed in the background population [ 2 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of undiagnosed CD are not well described. Studies have shown that patients with CD have an increased risk of other autoimmune diseases and gastrointestinal cancer [ 26 , 27 , 28 ]. One study found a fourfold increased mortality in persons with untreated and undiagnosed CD [ 29 ], whereas others reported mortality rates to be relatively similar to those observed in the background population [ 2 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Paimela et al [47] reported that AGA (IgA and/or IgG) was positive in 37% of patients with rheumatoid arthritis and in 12% of healthy controls. However, in a recent study on 190 patients with some autoimmune rheumatologic diseases (systemic lupus erythematosus, rheumatoid arthritis, juvenile rheumatoid arthritis, and spondyloarthrophathies), antigliadin IgA or IgG antibodies were found to be positive only in 4 and 3 patients, respectively [48]. The pronounced difference between the results of these studies may be explained by the difference in disease groups and variations in autoimmunity mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 27 studies comprising 28 articles were included in the model [ 50 , 52 , 54 , 55 , 66 , 69 , 71 74 , 78 , 80 , 82 , 83 , 85 87 , 89 , 90 , 94 , 97 , 100 , 114 , 116 – 118 , 121 , 122 ]. The work of Remes-troche, et al .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 49 studies were included in this model [ 50 , 52 55 , 58 73 , 75 , 77 , 79 81 , 83 , 85 , 88 , 90 , 94 , 96 , 99 102 , 104 , 107 , 109 – 113 , 116 – 121 ]. Within three studies obtained from the systematic review, the population was divided into subpopulations.…”
Section: Resultsmentioning
confidence: 99%